2014
DOI: 10.5194/acp-14-245-2014
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reaction of N<sub>2</sub>O<sub>5</sub> with illite and Arizona test dust particles

Abstract: Abstract. The heterogeneous reaction of N 2 O 5 with airborne illite and Arizona test dust (ATD) particles was investigated at room temperature and at different relative humidities using an atmospheric pressure aerosol flow tube. N 2 O 5 at concentrations in the range 8 to 24 × 10 12 molecule cm −3 was monitored using thermal-dissociation cavity ring-down spectroscopy at 662 nm. At zero relative humidity a large uptake coefficient of N 2 O 5 to illite was obtained, γ (N 2 O 5 ) = 0.09, which decreased to 0.04 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 61 publications
4
46
1
Order By: Relevance
“…FTIR observations showed that surface OH groups on Saharan dust particles were depleted during the exposure to N 2 O 5 , leading to the decrease of γ (N 2 O 5 ) with reaction time (Seisel et al, 2005). The uptake coefficient of N 2 O 5 onto illite was found to decrease with increasing RH, and this is suggested to be due to the coverage of OH groups by adsorbed water at high RH (Tang et al, 2014). The minimum of γ (N 2 O 5 ) onto TiO 2 at 20 % RH may indicate that the increase of RH up to 20 % could cause the more reactive surface OH groups to be covered by surface-adsorbed water, while further increase in RH will promote the heterogeneous hydrolysis of N 2 O 5 by surface-adsorbed water, i.e.…”
Section: Effects Of Relative Humiditymentioning
confidence: 90%
See 3 more Smart Citations
“…FTIR observations showed that surface OH groups on Saharan dust particles were depleted during the exposure to N 2 O 5 , leading to the decrease of γ (N 2 O 5 ) with reaction time (Seisel et al, 2005). The uptake coefficient of N 2 O 5 onto illite was found to decrease with increasing RH, and this is suggested to be due to the coverage of OH groups by adsorbed water at high RH (Tang et al, 2014). The minimum of γ (N 2 O 5 ) onto TiO 2 at 20 % RH may indicate that the increase of RH up to 20 % could cause the more reactive surface OH groups to be covered by surface-adsorbed water, while further increase in RH will promote the heterogeneous hydrolysis of N 2 O 5 by surface-adsorbed water, i.e.…”
Section: Effects Of Relative Humiditymentioning
confidence: 90%
“…The kinetics of the uptake of N 2 O 5 onto desert dust particles and their surrogates (e.g., Arizona Test Dust, illite) has been reported by several previous studies (Karagulian et al, 2006;Mogili et al, 2006;Seisel et al, 2005;Tang et al, 2010Tang et al, , 2012Tang et al, , 2014Wagner et al, 2008Wagner et al, , 2009). In addition, Seisel et al (2005) observed the formation of nitrate on mineral dust particles due to the uptake of N 2 O 5 using diffuse reflectance FTIR (Fourier transform infrared spectroscopy), and Tang et al (2012) further confirmed that the yield of nitrate is ∼ 2 (as expected from Reaction R1) within the experimental uncertainty, and that the formation of NO 2 is negligible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…large uptake coefficients) and big particles, gas phase diffusion of X can limit the overall rate of the uptake of X onto the surface. A method used to calculate diff for poly-dispersed aerosol particles has also been developed (Tang et al, 2012(Tang et al, , 2014. As shown in Eqs.…”
Section: Introductionmentioning
confidence: 99%